Do Capital Structure, Profitability and Earnings Volatility Affect Firm Value? Moderating Role of CSR Disclosure in Indonesia’s Non-Financial Industry - Liani; Azazi, Anwar; Rosnani, Titik; Ristyawan, M. Ridwan; Syahputri, Anggraini (Universitas Muhammadiyah Pontianak, 2026)
In highly competitive global business era, maximizing firm value is key to competitive advantage and sustainability. This study examines the impact of capital structure, profitability and earnings volatility on firm value with moderating role of CSR Disclosure among Indonesia’s energy, basic materials and non-cyclical sectors listed at Indonesian Stock Exchange (IDX) from 2021-2024. Data from annual and sustainability reports were tested using multiple linear regression on E-views. Results indicate that capital structure, profitability and earnings volatility significantly impacting firm value, while CSR only moderate capital structure and profitability. This suggests that investors may prioritize financial performance when assessing firm value. Keywords: Capital Structure; Profitability; Earnings Volatility; Firm Value; CSR